2022
DOI: 10.1136/lupus-2021-000651
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine in the pregnancies of women with lupus: a meta-analysis of individual participant data

Abstract: ObjectiveMultiple guidelines recommend continuing hydroxychloroquine (HCQ) for SLE during pregnancy based on observational data. The goal of this individual patient data meta-analysis was to identify the potential benefits and harms of HCQ use within lupus pregnancies.MethodsEligible studies included prospectively collected pregnancies in women with lupus. After a systematic literature search, seven datasets meeting inclusion criteria were obtained. Pregnancy outcomes and lupus activity were compared for pregn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 52 publications
0
16
0
3
Order By: Relevance
“…In a large individual-patient meta-analysis of 983 pregnancies in 804 women, we demonstrated that hydroxychloroquine did not lower rates of preeclampsia among women with SLE. 16 In this study, patients had high rates of exposure to hydroxychloroquine but also found no difference in the incidence of preeclampsia in patients who were prescribed hydroxychloroquine compared to those who were not. Regardless, hydroxychloroquine should be continued during pregnancy to avoid lupus flares.…”
Section: Discussionmentioning
confidence: 49%
“…In a large individual-patient meta-analysis of 983 pregnancies in 804 women, we demonstrated that hydroxychloroquine did not lower rates of preeclampsia among women with SLE. 16 In this study, patients had high rates of exposure to hydroxychloroquine but also found no difference in the incidence of preeclampsia in patients who were prescribed hydroxychloroquine compared to those who were not. Regardless, hydroxychloroquine should be continued during pregnancy to avoid lupus flares.…”
Section: Discussionmentioning
confidence: 49%
“…The authors highlighted the limitations of observational data in studying the impact of medications on pregnancy outcomes as they are subjected to bias by indication and limited data on adherence. 36 This study has several advantages: the large number of included patients, the prospective study design allowing for accurate data collection, and the availability of a dedicated team of rheumatologists and obstetricians allowing for close follow-up and timely and effective management of maternal and fetal complications.…”
Section: Discussionmentioning
confidence: 99%
“…The authors highlighted the limitations of observational data in studying the impact of medications on pregnancy outcomes as they are subjected to bias by indication and limited data on adherence. 36…”
Section: Discussionmentioning
confidence: 99%
“…AGG -EMPFEHLUNG (20) Bei Frauen mit positiven SS-A-und/oder SS-B-Antikörpern sollte die prophylaktische Therapie mit 400 mg/d HCQ diskutiert und großzügig empfohlen werden.…”
Section: Agg -Empfehlung (19)unclassified